1997
DOI: 10.1038/bjc.1997.17
|View full text |Cite
|
Sign up to set email alerts
|

Changes in nutritional status associated with unresectable pancreatic cancer

Abstract: Summary Weight loss is common in patients with pancreatic cancer; however, the nature and progress of their nutritional depletion are not well documented. In this study, pre-illness weight and duration of weight loss were recorded in 20 patients with histologically confirmed unresectable cancer of the pancreas. Patients then underwent nutritional analysis at monthly intervals until death. The median period of assessment was 27 weeks (interquartile range 22.5-38.0 weeks). At the time of diagnosis, all patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
136
0
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(144 citation statements)
references
References 24 publications
4
136
0
4
Order By: Relevance
“…Malnourished cancer patients may have a BMI within the healthy or overweight range, with body fat masking loss of lean body mass. Wigmore et al (1997) found that the median BMI of 20 pancreatic cancer patients at diagnosis was 20.7 (range 19.5 -23.6) kg=m 2 despite a median weight loss of 14.2 (range 10 -20%) in the previous 6 months.…”
Section: Discussionmentioning
confidence: 93%
“…Malnourished cancer patients may have a BMI within the healthy or overweight range, with body fat masking loss of lean body mass. Wigmore et al (1997) found that the median BMI of 20 pancreatic cancer patients at diagnosis was 20.7 (range 19.5 -23.6) kg=m 2 despite a median weight loss of 14.2 (range 10 -20%) in the previous 6 months.…”
Section: Discussionmentioning
confidence: 93%
“…More than 80 % of patients with pancreatic cancer (PC) suffer from significant weight loss at the time of diagnosis [1]. The aetiology of this prominent feature may be multi-factorial and is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Co ważne, nie ma żadnych wiarygodnych danych wskazujących na to, że leczenie żywieniowe ma wpływ na pobudzanie wzrostu nowotworu, czyli przyspieszenie rozwoju choroby, chociaż nie można wykluczyć stymulującego wpływu niektórych składników odżywczych na wzrost nowotworu [2]. Z kolei niedobór składników odżywczych w sposób oczywisty nie tylko nie hamuje rozwoju nowotworu, ale także istotnie pogarsza stan chorego, zmniejsza tolerancję leczenia onkologicznego, zwiększa ryzyko wystąpienia powikłań i może prowadzić do przerwania leczenia przeciwnowotworowego, a w skrajnych przypadkach nawet do zgonu [5][6][7][8][9]. Niedożywienie jest także niezależnym negatywnym czynnikiem prognostycznym i zwiększa ryzyko wystąpienia toksyczności leczenia przyczynowego [10][11][12].…”
Section: Określenie Wskazań Do Leczenia żYwieniowegounclassified